KEANEKARAGAMAN MAKROZOOBENTOS DI DANAU TOBA DESA HARANGGAOL KECAMATAN HARANGGAOL HORISAN KABUPATEN SIMALUNGUN - Ariance Nurdaya Sitanggang; Hasan Sitorus; Riri Ezraneti (AQUACOASTMARINE, 2014)
The aims of study were to determine the diversity of macrozoobenthos and to analize the relationship of water quality parameters (temperature, pH, DO, BOD5) to diversity index of macrozoobenthos in Lake Toba , Village Haranggaol, Haranggaol Horisan Subdistrict, Simalungun District. Observations had been carried out three times in three locations, and each location sampling was conducted three replications. Regression analysis was used to determine the correlation of water quality parameters to diversity index of macrozoobenthos. Based on the research obtained that macrozoobenthos diversity index ranged from 1.53 to 1.90, uniformity index ranged from 0.82 to 0.95, the population density ranges from 332 to 645 ind/m2 and relative density ranged from 99.95 to 99.98 %. Regression analysis showed that the correlation coefficient (R) of 0.710 indicates that the relationship between water quality against the relatively strong macrozoobenthos diversity index and the coefficient of determination (R2) obtained at 0.505.Keywords: Diversity, Lake Toba, Macrozoobenthos.